Synthesis and characterization of the Bi2Ce2-xZrxO7 pigments - Těšitelová, Kateřina; Šulcová, Petra; Koláčková, Iva (My University, 2016)
This contribution is focused on the synthesis, characterization and optical properties of new inorganic pigments. The pigments were prepared by the solid-state reaction. The colour properties of prepared applications were investigated depending on the content of Zr and temperature of calcination (800-1000 °C after step 50 °C). The optimum conditions for the pigments synthesis were determined.
Syntéza a charakterizace pigmentů Bi2Ce2-xZrxO7
Keywords: Bismuth Mixed Oxides; Inorganic Pigments; Pyrochlore Compounds; Colour Properties; Yellow Colour; směsné pigmenty na bázi bismutu; anorganické pigmenty; Pyrochlorové sloučeniny; barevné vlastnosti; žlutá barva